2019
DOI: 10.1186/s13104-019-4066-x
|View full text |Cite
|
Sign up to set email alerts
|

Community-Led Total Sanitation and the rate of latrine ownership

Abstract: ObjectiveLack of sanitation affecting billions of people worldwide is a serious public health problem of Ethiopia. So, we aimed at examining the influence of community interventions on households’ latrine ownership status in Northwest Ethiopia.ResultsThe proportion of households owning latrines were 47% (95% CI 42.5, 52.0). Community Lead Total Sanitation practice in the kebele [AOR = 1.78, 95% CI (1.57, 2.03)], health facilities available in the village [AOR = 2.37, 95% CI (2.14, 2.64)], and increased educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
1
18
1
Order By: Relevance
“…Accordingly, latrine prevalence was almost consistent with the national estimate (44%) as documented in EDHS, 2016 [7]. Similar evidence was reported from South East Zone of Tigray, Northern Ethiopia (37.6%), Central Zone of Tigray, Northern Ethiopia (37.4%), and Dabat district, North West Ethiopia (47%) [11,25,26].…”
Section: Discussionsupporting
confidence: 83%
“…Accordingly, latrine prevalence was almost consistent with the national estimate (44%) as documented in EDHS, 2016 [7]. Similar evidence was reported from South East Zone of Tigray, Northern Ethiopia (37.6%), Central Zone of Tigray, Northern Ethiopia (37.4%), and Dabat district, North West Ethiopia (47%) [11,25,26].…”
Section: Discussionsupporting
confidence: 83%
“…Some participants cited problems in procuring materials to build a latrine or the price tag of constructing a latrine as a barrier. Ethiopia at present encourages a simple pit latrine with a slab made from locally obtainable materials [ 37 ]. Even though the use of locally obtainable materials has been advocated for the sustainability of any embraced technology, the present study revealed that latrines fell short of being sustained as a result of the use of poor quality local materials.…”
Section: Discussionmentioning
confidence: 99%
“…They spread innovations by using their shared knowledge of the language, social, cultural and religious beliefs and their existing relationships with and within communities (30,31). Innovators and early adopters in a community include teachers (30,55), leaders (10,22,30,31,34,55,56), healthcare workers (30,42,55,57,58), and community committees (21,46,59,60). Diffusion can contribute to the three outcomes -access, change and sustainability.…”
Section: Diffusionmentioning
confidence: 99%
“…Without external support, shame can promote access to and individual/household ownership of latrines (22,31,38,55,57,62,65,77) and handwashing facilities (30,33,62). These outcomes are limited in communities and households with financial and technical challenges (24,35,61,65).…”
Section: Accessmentioning
confidence: 99%
See 1 more Smart Citation